COMPARATIVE PERFORMANCE OF GUINEA KEETS MANAGED UNDER 2 BROODING SYSTEMS IN THE TOLON DISTRICT OF NORTHERN REGION OF GHANA - Mohammed, A.; Dei, H. K. (UDS International Journal of Development, 2017)
A study was conducted to assess the effects of improved brooding and management on survivability and performance of guinea keets in the Tolon District of the Northern Region of Ghana. Ten farmers (7 men and 3 women) were purposively sampled for the study. One thousand, six hundred (1600) mixed sex day-old guinea keets (i.e. local strain) were randomly allotted into 20 groups of 80 keets per group and assigned to 2 treatments using a Randomized Complete Block Design with a farmer serving as a block. Treatment 1 (Control) was the traditional brooding (i.e. using mother hen) and birds managed under the semi-intensive system and Treatment 2 was the improved brooding (i.e. confined in raised wire floor cages covered with black polythene sheet) and birds managed under the intensive system. Growth and mortality data collected were subjected to a two-sample test using Studentized T-test. Treatment 2 keets were 68.78% heavier (P<0.001) than their treatment 1 counterparts at 8 weeks of age. Mortality records in treatment 2 was 81.68% lower (P<0.001) than the treatment 1 group. The results show that it was beneficial to brood keets using the improved cage system than the traditional system of brooding. Keywords: Brooding, Growth performance, Guinea keets, Management, Survivability